The Edmonton Obesity Staging System Predicts Postoperative Complications After Abdominoplasty. Issue 5 (November 2021) - Simunovic, Filip; Bonaventura, Bastian; Schneider, Laura; Horner, Verena K.; Weber, Janick; Stark, G. Björn; Kalash, Ziad
Abstract : Background: This study investigates the relationship between Edmonton Obesity Staging System (EOSS) and the occurrence of postoperative complications after abdominoplasty in massive weight loss patients. Methods: A single-institution retrospective review of patients undergoing abdominoplasty between 2009 and 2019 after massive weight loss. Demographic data, laboratory findings, known risk factors for postoperative complications, as well as data on major and minor complications were extracted from the patient charts. Logistic regression models were used to investigate the relationship between the variables. Results: Four hundred and five patients were included in the study. The prevalence of EOSS stages was: 0 (no comorbidities, N = 151, 37%), 1 (mild conditions, N = 40, 10%), 2 (moderate conditions, N = 149, 36%) and 3 (severe conditions, N = 70, 17%). Regression analysis showed that, controlling for body mass index (BMI), BMI Δ (maximal BMI − BMI at presentation), bariatric surgery, volume of resected tissue, and duration of surgery, EOSS stage significantly associated with the occurrence of postoperative complications. Compared with EOSS stage 0, EOSS stages 2 and 3 patients were associated with significantly more minor and major complications, respectively. The volume of resected tissue, BMI Δ, and age were associated with the occurrence of major complications. A regression model of comorbidities comprising the EOSS revealed a significant association of variables diabetes mellitus and hypertension with the occurrence of postoperative complications. Conclusions: Edmonton Obesity Staging System is a robust predictor of postoperative complications in abdominoplasty. Abstract : Supplemental digital content is available in the text.